LAMPUNG CLAUSE COMPLEXES: A PARATACTIC CONFIGURATION STUDY - Afrianto Afrianto; Farida Ariyani; Ingatan Gulo (LITERA, 2022)
This research aims at capturing and characterizing clause complexes in Lampung language by considering the structure and conjunction. Here, it focuses on paratactic configuration. A Lampung paratactic configuration consists of two or more independent clauses and is also recognized by the presence of conjunction and punctuation. The conjunction bridges two or more clauses in clause complexes and signs a relation between and among those clauses. There are six conjunctions found; those are ‘ghik’, ‘kidang’, ‘tapi’, ‘sedengko’, ‘jadi’, and ‘bahko’. Regarding how those conjunctions relate clauses, this research found four types of relation; those are additional relation realized by ‘ghik’ and ‘bahko’, comparative and contrastive relation performed by ‘kidang’, ‘tapi’, ‘sedengko’ and then consequential relation shown by ‘jadi’. Other than conjunction, the punctuation is also found to connect clauses; it is comma. It is noteworthy that comma connects two independent clauses and semantically construes additional relation since comma is found in configuration of two clauses in which a clause adds more detail information or more explanation for another one. Besides, comma is also found in a paratactic configuration consisting of three clauses, here it is configured with a conjunction such as ‘ghik’. Furthermore, this research also found four variants of paratactic configuration; those are Independent clause - conjunction - Independent clause; Independent clause - conjunction - Independent clause + dependent clause; Independent clause + Dependent cause - conjunction - Independent clause; Independent clause + Dependent clause - conjunction - Independent clause + Dependent clause.